Sitting vs. standing isokinetic trunk extension and flexion performance differences - Findley, B. W.; Brown, L. E.; Whitehurst, M.; Gilbert, R.; Groo, D. R.; O'Neal, J. (The Journal of Strength and Conditioning Research, 2000)
Isokinetic trunk extension and flexion have traditionally been measured in either the sitting or standing position. However, these positions may produce dissimilar levels of peak torque (PT), work (W), and power (P). The purpose of this study was to determine if differences in these parameters existed between sitting and standing isokinetic trunk extension and flexion exercise. Sixteen subjects (8 men and 8 women, ages 30.8 ± 6.4 years, height 170.2 ± 11.0 cm, weight 68.0 ± 13.8 kg), performed 3 maximal repetitions of isokinetic concentric/concentric trunk extension and flexion at 120 and 60 d·s1 in the sitting and standing positions. Results revealed that standing flexion elicited significantly (p < 0.01) greater PT, W, and P values than sitting at both speeds tested, whereas no ifferences were noted in extension. This suggests that the distinct muscle length tension relationships between the sitting and standing positions elicit unique torque outputs during trunk flexion. Therefore, caution should be exercised when interpreting position-specific isokinetic test results that measure trunk flexion.